The Impact of Psychological Factors on the Purchasing Desire Among Members of the Saudi Society In the period between 2021 - 2023 AD - Al-Ghamdi, Bandar AbdulRahim (Journal of Economic, Administrative and Legal Sciences, 2024)
The present study aimed to identify the impact of psychological factors on the purchasing desire among members of Saudi society In the period between 2021 - 2023 AD. The researcher adopted the descriptive analytical approach and used a questionnaire to collect data. The study sample consisted of (100) individuals from Saudi society. The most important conclusions indicated that the level of responses to the items of the independent variable (Psychological Factors) was extremely, at a rate of 81.12% and the level of responses to the dependent variable (Purchasing Desire) was extremely, at a rate of 82.38%. There is a statistically significant effect of psychological factors on the individual’s perception of their needs for the product to be purchased, and there is a statistically significant effect of psychological factors on an individual’s search for information about the product they want to buy. There is a statistically significant effect of psychological factors on the individual’s evaluation of the product they want to buy. There is a statistically significant effect of psychological factors on the individual’s decision-making decision for the product they want to buy. The study recommended the need to provide access to available products to increase desire and arouse interest among consumers, and the need to select products that are compatible with the continuous change in their personal desires.